Comparative statistical inference - Barnett, Vic. (Chichester ; New York : Wiley, 1999)
Presents a wide ranging, balanced account of the fundamental issues across the full spectrum of inference and decision--making. It also presents the basic conceptual and interpretative distinctions between the different approaches, how they interrelate, what assumptions they are based on, and the practical implications of such distinctions.
Includes bibliographical references (p. [337]-364) and index.
oif 04/05/15
Loan
Keywords: Mathematical statistics; Statistical decision